2016
DOI: 10.1186/s40550-016-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence of organochlorine pesticides in xoconostle (Opuntia joconostle) in the central region of Mexico

Abstract: Background: Mexico has many natural resources for use in the food industry. In recent years Xoconostle, which is considered as a traditional food, has gained importance due to key its components such as fiber, antioxidants, and fermentative bacteria found in both the peel and fruit, which could benefit human and animal health. Information on the presence of organic contaminants such as pesticides in Xoconostle is important in protecting its reputation as a healthy food. The objective of this research was to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Two samples RVS 1 (0.460 mgkg −1 ) for permethrin and RVS 3 (0.179 mgkg −1 ) for diazinon from farm sites in KNUST and Chirapatre exceeded their respective MRL. The other samples (RVS 12 and 13 for chlorpyrifos, RVS 15 for deltamethrin, RVS 11 for Pérez et al (2016) processes such as blanching, cooking, frying, peeling and washing reduces pesticide residue levels in fruits and vegetables. Pesticide residues that are loosely attached to the surface were observed to be reduced by washing while peeling removes even those that have penetrated the cuticles of the fruits or vegetables.…”
Section: Pesticide Residuesmentioning
confidence: 99%
“…Two samples RVS 1 (0.460 mgkg −1 ) for permethrin and RVS 3 (0.179 mgkg −1 ) for diazinon from farm sites in KNUST and Chirapatre exceeded their respective MRL. The other samples (RVS 12 and 13 for chlorpyrifos, RVS 15 for deltamethrin, RVS 11 for Pérez et al (2016) processes such as blanching, cooking, frying, peeling and washing reduces pesticide residue levels in fruits and vegetables. Pesticide residues that are loosely attached to the surface were observed to be reduced by washing while peeling removes even those that have penetrated the cuticles of the fruits or vegetables.…”
Section: Pesticide Residuesmentioning
confidence: 99%
“…Washing fresh tomato and its inability to transmit diseases to consumers has been demonstrated by number of studies as providing safe vegetables for consumption. Perez et al (2016) in Mexico agreed with washing of vegetable as a practice preventing any human health infection with pesticides residues because those on the surface are usually removed. Their finding concurs with Akomea-Frempong et al (2017) in Ghana who found multiple pesticide residues and molecules above MRLs in vegetables ready to eat and concluded that, consumers are not at risk of pesticides related diseases if they wash their crops with running water.…”
Section: Consumers' General Awareness Of Pesticides and Pathogens On mentioning
confidence: 99%
“…Morelos State produces 30.9% of the edible nopalitos (young pads) of the country (3,905 ha) with an annual production of 367,836 tons (SIAP 2018). Traditional pests in the region are the cactus weevil, Cactophagus spinolae (Gyllenhal) (Coleoptera: Dryophthoridae) (López-Martínez et al 2016), cochi-neal scale insect, Dactylopius opuntiae (Cockerell) (Hemiptera: Dactylopiidae) (Vanegas-Rico et al 2010), and a thrips species, Sericothrips opuntiae Hood (Thysanoptera: Thripidae) (Pérez et al 2016). Their periodical damage requires control strategies to reduce their economic and environmental impact.…”
Section: First Report Of Range Expansion Of the Cactus Webworm Loxommentioning
confidence: 99%